MENINGKATKAN PROSES DAN HASIL BELAJAR IPA KELAS IV SD MENGGUNAKAN METODE COURSE REVIEW HORAY - Nofitaria Nofitaria; Sundahry Sundahry; Apdoludin Apdoludin; Yogi Irdes Putra (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of this study is to describe the improvement of fourth-grade student learning outcomes. This research is a type of classroom action research that is carried out in two cycles, each cycle consisting of two meetings. Each cycle consists of planning, implementing, observing, and reflecting. The results of data analysis show that the use of the Course Review Horay method can improve the processes and results of learning science for students in class IV SDN 094/II Muara Bungo. Based on the results of the study, details of the observations of educators in cycle I with an average educator activity of 96.99%, in cycle II the average educator activity is 96.99% with a very good category. The results of observations of students in the first cycle of data analysis of student activity by 62.5% increased to 80% in cycle II. While the classical completeness in the first cycle of 60% increased to 90% in the second cycle. It was concluded that the use of the Course Review Horay method could improve science learning processes and outcomes.